Valorization of Black Beans (Phaseolus vulgaris L.) for the Extraction of Bioactive Compounds Using Solid-State Fermentation - Dulce W. González-Martínez; Alma D. Casas-Rodríguez; Sergio A. Coronado-Contreras; Adriana C. Flores-Gallegos; Claudia M. López-Badillo; Juan A. Ascacio-Valdés; Antonio Flores-Naveda; Leonardo Sepúlveda (Waste, 2025)
Black beans (Phaseolus vulgaris L.) are one of the most consumed legumes worldwide. Black beans are rich in proteins, vitamins, minerals, and polyphenolic compounds. The present study aims to valorize black beans for the extraction of polyphenolic compounds using solid-state fermentation (SSF) from Aspergillus niger GH1. A physicochemical analysis of black beans was performed. Fermentation kinetics was performed to establish the best accumulation time of condensed polyphenols. A two-level Plackett–Burman experimental design was used to evaluate the culture conditions (temperature, humidity, inoculum, particle size, pH and salt concentration) for the accumulation of condensed polyphenols. The results of the physicochemical analysis showed that black beans can be used as a substrate in the SSF process. In addition, the best time for the accumulation of condensed polyphenols was 48 h. Treatment 5 achieved an accumulation of 21.04 mg/g of condensed polyphenols. While the factors of particle size, humidity, and temperature had a significant effect on the accumulation of condensed polyphenols. It is concluded that the SSF process is an efficient and eco-friendly extraction method for obtaining bioactive molecules with potential applications in the pharmaceutical, food, and cosmetic industries.